Splenic Artery Pseudoaneurysm Presenting as Massive Hematemesis: A Diagnostic Dilemma. (13th February 2014) - Varshney, Peeyush; Songra, Bhupen; Mathur, Shivank; Gothwal, Sudarshan; Malik, Puneet; Rathi, Mahnedra; Arya, Rajveer
Abstract : Introduction . Splenic artery Pseudoaneurysm, a complication of chronic pancreatitis, presenting as massive hematemesis is a rare presentation. Case Report . We present a case of 38-year-old male admitted with chief complaints of pain in the upper abdomen and massive hematemesis for the last 15 days. On examination there was severe pallor. On investigating the patient, Hb was 4.0 gm/dL, upper GI endoscopy revealed a leiomyoma in fundus of stomach, and EUS Doppler also supported the UGI findings. On further investigation of the patient, CECT of the abdomen revealed a possibility of distal pancreatic carcinoma encasing splenic vessels and infiltrating the adjacent structure. FNA taken at the time of EUS was consistent with inflammatory pathology. Triple phase CT of the abdomen revealed a splenic artery pseudoaneurysm with multiple splenic infarcts. After resuscitation we planned an emergency laparotomy; splenic artery pseudoaneurysm densely adherent to adjacent structures and associated with distal pancreatic necrosis was found. We performed splenectomy with repair of the defect in the stomach wall and necrosectomy. Postoperative course was uneventful and patient was discharged on day 8. Conclusion . Pseudoaneurysm can be at times a very difficult situation to manage; options available are either catheter embolisation if patient is vitally stable, or otherwise, exploration.